Forward-Backward Stochastic Differential Equations and Backward Linear Quadratic Stochastic Optimal Control Problem (Communications in Mathematical Research, 2021)
In this paper, we use the solutions of forward-backward stochastic differential equations to get the optimal control for backward stochastic linear quadraticoptimal control problem. And we also give the linear feedback regulator for the optimal control problem by using the solutions of a group of Riccati equations.
Keywords: backward stochastic differential equations; optimal control; Riccati equation.